STUDENTS’ PERCEPTION OF COMPUTER MEDIATED COMMUNICATION IN EFL READING CLASSROOM - Al Hakim, Luqman; Istiana Sari, Ayu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The implementation of autonomous learning needs various activities and media in order to attain learning outcomes. The article presents the research findings about the students’ perception toward autonomous learning through computer mediated communication (CMC). The research was carried out in the intensive reading lesson that consists of 14 meetings and 100 minutes each. The type of research is a descriptive qualitative. The participant in the research is 2nd semester students of bachelor degree of English language education at Slamet Riyadi University, Indonesia, who are 36 students. The research was done both offline and online learnings before and during corona pandemic situation in 2020. The methods of collecting the data are questionnaire after learning finished and observation in following the lesson. The researchers analyzed the data used data display, data reduction, and conclusion. The research findings show that there are various activities facilitating the students’ reading comprehension. They are online listening, text-based and video based CMC, collaborative activity, online chat log, and text based communication; the students have a responsibility to follow both offline and online learning activities by doing individual and collaborative activities, and the students use creative language and language strategy to communicate the texts’ content being learnt. Keywords: maximum 5 keywords, sort alphabetically